Correction to: heterosexual university students’ attitudes toward same-sex couples and parents across seven european countries - D'Amore, Salvatore (2021)
Introduction This research examined the general attitudes toward lesbian women and gay men (LG people), same-sex marriage (SSM), and LG parenting (LGP) in a large sample of young heterosexual European adults. We expected that one’s country of origin, gender role traditionalism, contact, and religiosity would predict their responses. Methods We conducted a large-scale study from April 2012 to November 2014. The sample consisted of 13,403 self-identified heterosexual students from Belgium, Italy, France, Portugal, Poland, Spain, and Greece (38.7% men and 61.2% women). The main research variables were general attitudes toward LG people, support for same-sex coupling and parenting, gender role traditionalism beliefs, frequency and quality of the contact with LG people, and religiosity. Results We found that the attitudes toward these issues were significantly more negative in Poland and Greece than in the other countries included in the sample. In addition, these national differences were explained by psychological variables, mainly religiosity and general attitudes toward LG people. Although participants’ higher satisfaction levels regarding their contact with LG people and lower levels of gender role traditionalism were associated with positive attitudes toward SSM and parenting, these factors did not account for the attitudinal variability between these countries. Conclusions Attitudes toward LG people are changing throughout Europe and are influenced by each country’s sociopolitical context. We highlight the societal importance of attitudes toward SSM and LG parenting and recommend facilitating positive social contact in universities and other settings to improve young adult heterosexuals’ attitudes. Policy Implications This study’s results can inform policies aiming to reduce inequality and develop more inclusive policies on same-sex parented families and couples.